DAYA HAMBAT SARI TANAMAN OBAT TERHADAP PERTUMBUHAN BAKTERI STRAIN Methicillin Resistant Staphylococcus aureus (MRSA) - Putri, Dwi Hilda; Fifendy, Mades; Febrianti, Rhini (Sainstek : Jurnal Sains dan Teknologi, 2010)
Staphylococcus aureus infection can be treated with Methicilin, ? lactam class of antibiotics that have drug targets in the cell wall. Bacteria S. aureus that is resistant to methicillin called methicillin-resistant Staphylococcus aureus (MRSA). One alternative that can be used in strains of antibiotic-resistant bacteria that have this is to use medicinal plants. This study aimed to know the ability of medicinal plant extracts inhibit the growth of bacterial strains of MRSA. This kind of research is experimental research. Medicinal plants tested were Garlic, Turmeric, Aloe Vera, Daun Salam, Curcuma, Ginger, Betel Leaf and Alpinia galanga. As a control, which is used Amphicillin, ? lactam antibiotic class. The method used to determine the diameter of inhibition area of medicinal plant extracts is paper diffusion method. The results showed that all medicinal plants can inhibit bacterial growth of MRSA strains characterized by the inhibition zone formed on each treatment. The ability of garlic and turmeric extract better than Amphicillin and other medicinal plants to inhibit bacterial growth of MRSA strains.Kata kunci: inhibit,  growth, bacteria, methicillin resistant staphylococcus aureus (MRSA)